Quantification of Chronic Oxaliplatin-Induced Hypesthesia in Two Areas of the Hand. Issue 2 (March 2017) - Andriamamonjy, Mihary; Delmotte, Jean-Baptiste; Savinelli, Francesco; Beaussier, Hélène; Coudoré, François
Abstract : Purpose: Oxaliplatin is a platinum derivate widely used in cancer treatment but producing dose-limiting peripheral neurotoxicity. Acute neuropathy is characterized by a transient cold-induced distal allodynia, whereas chronic neuropathy leads to sensory loss. To design a method for quantitative assessment of oxaliplatin-induced peripheral neuropathy, we developed a study that aims to characterize the most appropriate skin area of the hand to perform sensory tests. Methods: We included patients treated for at least 6 months with oxaliplatin. Thermal sensory tests are assessed using the Thermotest (Somedic) and consist in measuring thermal thresholds in the thenar and in the fingertips of the opposite hand. Results are analyzed using T-Tests comparing thermal sensory thresholds between the two areas of the hand, globally and then individually. Results: In 7 weeks, 12 patients (7 men and 5 women; mean age: 64.5 years) were included, all treated with FOLFOX protocol. Thermal detection thresholds measured on the fingertips are 146% and 108% greater than the ones measured on the palm for cold and warm, respectively ( P < 0.0001). Thermal pain thresholds are difficult to interpret. Regarding individual tests, 9/12 patients and 8/12 patients experienced hypesthesia to cold and warm, respectively. Conclusions: These results reveal that distal hypesthesia occurring under treatment with oxaliplatin is markedly pronounced in the fingertips; however, as thermal threshold is unknown before treatment, it is difficult to assert that fingertip thermal hypesthesia has developed under treatment. Finally, this short study may be useful to design a method for quantifying oxaliplatin-induced neuropathy.